The Tumbang Batu Model of Islamic Eco-Resistance: Interweaving Iḥsān and Indigenous Wisdom Against Extractive Development - Wakhidah, Nur; Alias, Muhammad Nazir; Safii, Safii (Journal of Malay Islamic Studies, 2026)
Environmental degradation in Kalimantan is not only an ecological crisis but also a challenge to the ethical foundations of local communities. This study aims to explore how the Muslim community in Tumbang Batu integrates local Dayak-Malay wisdom with the Islamic ethic of iḥsān in formulating resistance to the expansion of the palm oil industry. Using a qualitative approach and social construction theory, data were collected through in-depth interviews, participant observation, and documentation of community practices. The results reveal that forest preservation in Tumbang Batu is understood as "Ecological Marwah"—a sacred obligation that combines collective ancestral memory with a transcendental mandate. Key findings indicate the emergence of The Tumbang Batu Model of Islamic Eco-Resistance, where the value of iḥsān acts as a kinetic moral compass that encourages excellence and compassion for all creation. This phenomenon is also strengthened by the digital agency of youth through the concept of Sacred Environmental Cartography, which synergizes GPS mapping with sacred customary zones. This study concludes that the integration of vernacular theology and local epistemic sovereignty is key to the sustainability of a resilient ecosystem. This study makes a theoretical contribution to the global Eco-Islam discourse by offering a new paradigm in environmental policy based on hybrid identities and grassroots spirituality.